Numerical analysis of the penetration process of a 30mm armor-piercing projectile - Pantović, Predrag R.; Živković, Miroslav M.; Milovanović, Vladimir P.; Miloradović, Nenad M. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: Thin plates made of high–strength steel are frequently used both in civil and military ballistic protection systems. In order to choose an appropriate type of alloy, it is necessary to fulfil a number of criteria, such as the condition of use, the desired ballistic performance, weight, dimensions, and price. This paper presents a numerical analysis of the penetration ofa 30mm armor-piercing projectile with a velocity of 750m/s intosteel alloy Weldox 460plates of different thicknessesat a distance of 1000m .Methods: The analysis has been performed using numerical methods and finite element modeling to calculate stresses and deformation caused by the penetration effect. For defining material characteristics, the Johnson-Cook material model and the fracture of materials model have been used. In this paper, the software packages FEMAP and LS Dyna have been used for defining models and performing numerical calculations. Results: The results of the performed numerical analysis as well as the obtained stress and displacement values are presented for four different armor plate thicknesses: 30mm, 33mm, 34mm, and 40mm. The results show a penetration effect and an interaction between the projectile and the armor plate.Conclusion: Modeling the impact on armor-piercing obstacles is very complex, extensive, and demanding, and the formed models approximate the real problem of projectile penetration in a very successful way (or with a certain deviation). In recent times, the analysis using the finite element method has proven to be one of effective approaches to solving such and similar problems. The material and the dimensions of the obstacle, as well as the material and the ballistic parameters of the projectile have the greatest influence on projectile penetration. Keeping all the input parameters at the same level andincreasing the thickness of the target leads toits increased resistance to penetration.
Keywords: armor; projectile; penetration; Weldox 460; numerical methods